2019
DOI: 10.1080/1034912x.2019.1614153
|View full text |Cite
|
Sign up to set email alerts
|

Employing Social Network Analysis to Examine the Social Participation of Students Identified as Having Special Educational Needs and Disabilities

Abstract: The number of students with identified Special Educational Needs and Disabilities (SEND) in mainstream schools has been rising in the last three decades, primarily due to policy changes promoting inclusive education. However, many of these students remain socially isolated despite expectations that inclusion may lead to enhanced outcomes, particularly social outcomes. This paper draws on a study conducted in three countries; Cyprus, Spain, and Switzerland. A critical case study design, grounded in social capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…It would be important that teachers realise that they might have only marginal insights into students' friendship networks. To do so, Mamas et al (2019aMamas et al ( , 2019b provide a social network analysis toolkit to enable different stakeholders to work together to better understand the social dynamics in schools. Using toolkits like this may help teachers to objectify their primed appraisals of their classroom situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be important that teachers realise that they might have only marginal insights into students' friendship networks. To do so, Mamas et al (2019aMamas et al ( , 2019b provide a social network analysis toolkit to enable different stakeholders to work together to better understand the social dynamics in schools. Using toolkits like this may help teachers to objectify their primed appraisals of their classroom situation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SNAs are often used in surveys that include students with SEN (e.g. Avramidis et al 2017;Mamas et al 2019b). For instance, Schwab (2019) showed that around 15% of primary school students with SEN (mostly diagnosed with learning disabilities) in inclusive education do not have a single reciprocal friendship in their class (compared to 3.9% of students without SEN).…”
Section: Introductionmentioning
confidence: 99%
“…developing friendships and engaging with the peer group (Koster et al, 2009;Mamas, Schaelli et al, 2020;Schwab, 2015). Also important, the few studies available suggest that peer-related social experiences of students with SEN vary as a function of the structure of classroom social networks (Mamas et al, 2019;Mamas, Schaelli et al, 2020).…”
Section: What Are the Main Insights That The Paper Provides?mentioning
confidence: 99%
“…No obstante, a pesar de las bondades reconocidas por los estudios previos, los trabajos pioneros de Moolenaar et al (2010) y Mamas et al (2020) alertan sobre las complejas estructuras de relaciones que emergen en las redes sociales y la importancia de disponer de procedimientos analíticos que identifiquen la lógica de la estructura relacional y contenidos en las redes sociales. En concreto, señalan la necesidad de ampliar nuestra comprensión de patrones no identificados, detectar quiénes ostentan los perfiles (organizaciones, medios, personas o compañías) que son susceptibles de ser analizados por medio de programas computacionales, entre otras cuestiones.…”
Section: Redes Sociales Y Empleabilidad Inclusivaunclassified